PRINCIPAL-AGENT PREFERENCES IN IMPERFECT MARKETS: THEORETICAL ANALYSIS ON MURABAHAH AND IJARAH - Hechem Ajmi; Hassanuddeen Abdul Aziz; Salina Kassim; Walid Mansour (Bank Indonesia, 2019)
This paper aims to determine the optimal contract for the principal and the agent in imperfect market, when murabahah and ijarah are used. The financial contracting enforceability approach is employed to determine the contract that maximizes the value of the firm subject to agents’ constraints when the shock is low and high, and regarding market frictions. Furthermore, this approach allows us to assess the level of market frictions that agents may bear in case of low shock and high shocks. Findings reveal that the simulated values of the market frictions’ parameters for both contracts increase when moving from the low shock to the high shock. Such evidence implies that the agent is more likely to cheat and hide significant information about the project when the shock is high. As a response to this higher risk, the simulated values of the profit margin parameters for the principal rise also when the shock is high in order to compensate for the increase of market frictions and mitigate conflicts of interest. By comparing both contracts based on the simulated optimal values of the firm, it is noticeable that the gap between both contracts is very tight, which can be attributed to their common debt-based financial arrangements. However, the results show that ijarah allows the principal and the agent to generate the highest value in case of low shock and high shock, comparing to murabahah. Therefore, ijarah seems to be more attractive for the principal and the agent than murabahah.